Determination of the Relationship and Spatial Variations of Discharge and Suspended Sediment Values in Watersheds of Ardabil Province - ebrahim asgari; Seyed Zeynalabedin Hosseini; raoof mostafazadeh (جغرافیا و توسعه, 2020)
Understanding the status of discharge and sediment of watersheds area provides an understanding of the hydrological processes. Uniform assuming of discharge and sediment in a watershed leads to the application of unit planning and management for the entire watershed and leads to a failure to achieve the goals. The present study was conducted with the aim of studying spatial variations and zoning of discharge and sediment values in Ardabil province during 10 years (2005-2014) at 37 stations with hydrometry in Ardabil province. IDW interpolation methods, simple kriging, ordinary kriging and cokrigring were investigated to determine the best method for studying spatial variaions, discharge and sediment variables. Based on the results of the evaluation indices of IDW (RMSE=1.172, MAE=0.644, MBE=-0.2, MSE=1.373) and cokriging (RMSE=0.107, MAE=0.08, MBE=-0.001, MSE=0.011) and the correlation coefficient between measured and estimated values by IDW (r=0.429) and cokriging (r=0.554) respectively, as the best method for evaluating the discharge and sediment variables were chosen. Based on the results of the IDW method, the amount of digestion in the Western parts of Ardabil province is greater (4.84-5.8 m3/s), and in the central section, this amount is the lowest (0.04-1 m3/s). According to the results of the interpolation of the sediment variable with the cokrigring method in the Western and Southern parts of Ardabil province with a higher amount of sediment (0.16-0.19 ton/ha/year) and in the central parts of the sediment deposition (0.01-0.04 ton/ha/year).